ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013-2015 - Yanuarni PuspitaJati, 14.05.52.0127; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2018)
This study aims to examine the effect of firm size, capital structure and liquidity on firm value. The independent variables in this study are firm size, capital structure and liquidity. As for the dependent variable in this study is the value of the company. The study sample consisted of 145 manufacturing companies listed on the Indonesia Stock Exchange for the period of 2013-2015. The sampling technique was chosen by purposive sampling. Financial report data from Indonesia Stock Exchange. The method of analysis used in this study is multiple linear regression. The results of this study indicate that firm size has a positive and significant effect on firmvalue, capital structure has negative and insignificant effect to firm value, liquidity has positive and insignificant effect to firm value.Keywords: firm size, capital structure, liquidity and corporate value